EFFICACY OF ENGLISH LANGUAGE MODULES FOR NOVICE-COLLEGE STUDENTS: A PATHWAY TO READING SCIENTIFIC JOURNALS - Muyas; Khoirun Nisa‘; Siti Nurrotul Aini (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2024)
This study aims at investigating significant difference in reading scientific journals of Novice students o IAI Al Qolam Malang before and after using English language module as the treatment. Accordingly, thi current study employs pre experimental research design precisely One-Group Pretest-Posttest Design wit taking 25 ELT students of al Qolam University as the samples. Based on the result of statistica calculation it is discovered that the instruction using English language module is unable to improve th Novice students’ reading skill of scientific journals at IAI Al Qolam Malang..Key words: scientific journals, Novice students, English modul